2013
DOI: 10.1097/nna.0b013e3182942c8a
|View full text |Cite
|
Sign up to set email alerts
|

How Do Clinicians Assess, Communicate About, and Manage Patient Sleep in the Hospital?

Abstract: It is critical to inform clinicians on the importance of sleep, to standardize sleep assessment, and to facilitate collaboration among caregivers to promote sleep for hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 7 publications
0
37
1
Order By: Relevance
“…Clinicians typically receive little training regarding sleep or its importance. In fact, most clinicians do not assess or communicate about the patient's quality of sleep . Many may not know that there is little evidence of benefit of pharmacological sleep aids in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians typically receive little training regarding sleep or its importance. In fact, most clinicians do not assess or communicate about the patient's quality of sleep . Many may not know that there is little evidence of benefit of pharmacological sleep aids in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most clinicians do not assess or communicate about the patient's quality of sleep. 11 Many may not know that there is little evidence of benefit of pharmacological sleep aids in the hospital. For example, a recent report found, in contrast to the authors' hypothesis, no changes in sleep architecture or duration using 10 mg of zolpidem tartrate in postoperative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that healthcare professionals do not have sufficient knowledge to actively work to promote patients' sleep (Hopper, Fried, & Pisani, 2015;Radtke, Obermann, & Teymer, 2014) and show that patients' sleep is not explicitly incorporated as a subject in nursing education (Huang, Liao, Chang, & Lai, 2018;McIntosh & MacMillan, 2009). Ye et al (2013)…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Studies indicate that healthcare professionals do not have sufficient knowledge to actively work to promote patients’ sleep (Hopper, Fried, & Pisani, ; Radtke, Obermann, & Teymer, ) and show that patients’ sleep is not explicitly incorporated as a subject in nursing education (Huang, Liao, Chang, & Lai, ; McIntosh & MacMillan, ). Ye et al () found that healthcare staff do not discuss sleep with patients enough and do not use assessment tools to identify and initiate nursing interventions to promote better sleep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation